Pain-relieving effects of pulsed magnetic fields in a rat model of carrageenan-induced hindpaw inflammation. (January 2014) - Mert, Tufan; Ocal, Isil; Cinar, Ercan; Yalcin, M. Serkan; Gunay, Ismail
Abstract Purpose: Many strategies have been investigated to exclude the several side-effects of pharmacological or invasive treatments. Non-invasive pulsed magnetic field (PMF) treatment with no toxicity or side-effects can be an alternative to pharmacologic treatments. The purpose of this study was, therefore, to investigate the pain-relieving effects of PMF treatment in the inflammatory pain conditions. Materials and methods: Effects of PMF treatment on the hallmarks of the inflammatory pain indices such as hyperalgesia, allodynia, edema and several biochemical parameters that evaluate oxidative stress were investigated using a well established carrageenan (CAR)-induced hindpaw inflammation model in rats. Results: CAR injection lowered the paw withdrawal thermal latencies (hyperalgesia) and mechanical thresholds (allodynia). CAR also decreased the superoxide dismutase (SOD), catalase (CAT) and glutathione peroxidase (GPx) levels and increased malondialdehyde (MDA) levels compared with healthy rat paw tissues. PMF treatment produced significant increases in the thermal latencies and mechanical thresholds in CAR-injected paws. In the inflamed paw tissues, PMF increased the activities of SOD, CAT and GPx and decreased MDA level. We also demonstrated that PMF decreased paw mass indicating that it has an anti-edematous potential. Conclusions: The present results reveal that PMF treatment can ameliorate the CAR-induced inflammatory pain indices such as mechanical allodynia, thermal hyperalgesia and edema, and attenuate the oxidative stress. The action mechanisms of PMF in CAR-induced inflammation might be related to the increases in the levels of antioxidant enzymes in inflamed tissues. The findings suggest that PMF treatment might be beneficial in inflammatory pain conditions.